Congenital Anomalies From the Embryo to the Neonate - Tudorache, Stefania (IntechOpen, 2018)
Nowadays, nobody can imagine practicing obstetrics without using obstetrical ultrasound. Working in the prenatal diagnosis field requires dedication, patience, skills, experience, caution, and empathy. The concept of this book was guided by the desire to provide some help to the ultrasound operators. On a daily basis, they are confronted with the challenging task of ruling out or suspecting/confirming the diagnosis of fetal anomalies, either structural or chromosomal. The chapters of this book contain objective and exhaustive updated reviews of the pertinent literature, so that the reader would have a wide reference basis on each subject. Yet, many authors scan the fetus themselves or are directly involved with managing pregnancies with structural malformations or chromosomal anomalies. They kindly shared their personal experience and lessons learned over the years. This book is beneficial for all the professionals working in the prenatal diagnosis.